Effectiveness of antibacterial dental brushes. In vitro study - Cadena, Eliana; Delgado, Jessica; Peña, Diana; Sánchez, Paola; Gutiérrez, Sonia; Contreras, Adolfo; Jaramillo, Adriana; Contreras, Anilza Bonelo (Revista Estomatología, 2014)
Objective: Toothbrush contamination is important to the oral health and the general health. Toothbrush is recommended to the regular elimination of the bacterial plaque; however it is also a potential source infection since it gets contaminated. Antibacterial toothbrushes were introduced to control the microbial contamination. Materials and methods: The effectiveness of antibacterial toothbrushes on the growth inhibition of A. actinomycetemcomitans, and E. cloacae were determined. This study included, three brands of dental brushes which were Oral-B® antibacterial Colgate® antibacterial I and as control one conventional dental brush non-antibacterial of Colgate. Materials and methods: A total of 48 dental brushes were inoculated, 24 with A. actinomycetemcomitans and 24 with E. cloacae and the microbial viability was established after diverse times as follows: 24 hours, 4 days, 12 days and 24 days, in an experiment for duplicate, evaluating the bacterial growth. Results: At 24 hours the dental brushes fulfill their antibacterial efficacy including the conventional dental brush, The Oral-B® antibacterial toothbrush and the Colgate® antibacterial controlled completely the growth of the colonies of the A. actinomycetemcomitans, while the Oral-B antibacterial toothbrush allowed E. cloacae’s growth. Finally after 24 days it was found that the inoculation the dental brushes does not inhibited either the A. actinomycetemcomitans or neither the E. cloacae. Conclusions: The antibacterial brushes are able to inhibit the growth of A. actinomycetemcomitans between 24 hours to 4 days, but this antibacterial effect is lost over the time. A super-infectious microorganism such as E. cloacae is more resistant to antibacterials present on dental brushes.